The effects of including nurse-led cognitive behavioural therapy groups compared to a standard nursing programme for inpatients with mood disorders - Visagie, Hester Maria Petronella (My University, 2017)
Background: The delivery of cost effective quality mental health care services pose a significant challenge in the South African public sector due to limited resources and unequal access to specialised mental health care services. Professional mental health care nurses are well placed to provide psycho-social interventions, seeing that they play a vital role in the nursing care processes and as part of the multi-disciplinary inpatient treatment team. Cognitive behavioural therapy is described as the psychological therapy with the most solid evidence base pertaining to efficacy and effectiveness when treating mood disorders, specifically depressive disorders (Westbrook, Kennerley and Kirk, 2011:18). Anecdotal reports from patients and nursing personnel highlighted limited therapeutic interventions. Despite available evidence, cognitive behavioural group therapy does not form part of standard nursing care programmes in inpatient units for patients with mood disorders and depressive disorders. Aim and objectives: The purpose of the study was to examine whether nurse-led cognitive behavioural therapy groups in the standard nursing care programme would promote change in the core beliefs, coping behaviour and depressive symptoms of patients admitted to an inpatient unit for mood disorders and depressive disorders. The objectives were to: To obtain base-line data of the patient outcomes before and after the standard nursing programme; to compile appropriate measurable evidence based intervention for patients with mood disorders and depressive symptoms (Nurse-led Cognitive Behavioural Therapy Manual); examine whether statistically significant differences exist between the standard nursing programme and the nurse-led CBT nursing programme; assess the effectiveness of the nurse-led CBT group intervention programme and to discuss the field notes and supporting observations made during the intervention programme and recommendations for psychiatric nursing practice in the unit and future research. Method: A quantitative, quasi-experimental design was utilised (pre-test / post-test with a control group and experimental group). A non-probability convenient sampling method was used to select patients who were admitted with mood disorders and depressive symptoms from April 2015 to November 2015 (n=35) to participate in the study. One group (Control group, A) received the standard nursing programme and treatment as usual. Group (B) received the nurse-led cognitive behavioural group therapy sessions (experimental group). The validated and tested Beck Depression Inventory Scale - BDI was applied to assess and measure the existence and severity of depressive symptoms. The BDI scale consists of 21 iv questions and measured symptoms of depression according to categories relating to cognitive, affective, somatic and behavioural domains. Results: Although the statistically significant differences between groups were small and therefore could not be generalised to a larger population, the results were important for clinical practice. According to the findings of this study, there is a higher prevalence of mood disorders and depressive disorders amongst single, older and white Afrikaans-speaking females, which are not only important for practice but also for future planning and research. Relevance of the study: The results of this study showed that nurse-led cognitive behavioural (CBT) group sessions had positive effects on the patient‟s well-being by relieving the symptoms of depression and to provide the opportunity to develop life skills. Participation and facilitation of the nurse-led CBT groups‟ added value to professional mental health care nursing practice and the therapeutic milieu.
A research dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, July 2017.
Keywords: Nurse-led Cognitive Behavioral Therapy; Mental Health Services; Mood Disorders; Depressive Disorder